PARATHYROID ADENOMA WITH PATHOLOGICAL FRACTURE IN YOUNG ADULT: A CASE REPORT - Meydina, Vinda; Decroli, Eva; Aprilia, Dinda; Kam, Alexander; Efendi, Yanne Pradwi; Syahbuddin, Syafril (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Primary hyperparathyroidism is a condition of hypercalcemia caused by an increase in parathyroid hormone (PTH) levels. The most common cause of primary hyperparathyroidism is parathyroid adenoma (85%). Primary hyperparathyroidism often goes undiagnosed, particularly in fracture cases, which can lead to complications. CASE A 24-year-old female presented to the endocrinology clinic with complaints of worsening back pain and inability to walk over the past three months. The patient had a history of a fall six months prior and was treated in the orthopedic department. MRI of the lumbosacral region revealed multiple thoracolumbar vertebral fractures suspected to be due to osteoporosis. Laboratory tests indicated hypercalcemia (11.4 mg/dL) and hyperparathyroidism (PTH 791 ng/dL). Neck MRI suggested the presence of a left parathyroid adenoma. The patient was diagnosed with primary hyperparathyroidism due to a parathyroid adenoma and underwent parathyroidectomy. Two months after the procedure, her back pain was relieved and daily activity returned to normal. Laboratory test showed improvement of serum calcium level (8.7 mg/dL). CONCLUSION The presence of a pathological fracture in a young adult must raise suspicion for a possible parathyroid adenoma. The diagnosis of primary hyperparathyroidism is established based on clinical findings and laboratory tests of serum calcium and parathyroid hormone levels. Early diagnosis and definitive management with parathyroidectomy are required in patients with primary hyperparathyroidism to reduce complications and improve quality of life.